Colombia - The Quality of Education in Colombia : An Analysis and Options for a Policy Agenda - World Bank (Washington, DC, 2012)
The main objective of this report is to analyze student learning in Colombia in order to foster policies to improve education quality that are grounded in research and the Colombian context. In 2006, Colombia participated for the first time in the Programme for International Student Assessment (PISA) of the Organization for Economic Cooperation and Development (OECD), which provides an important opportunity to benchmark the quality and equity of its education system globally and to inform its education policy. Using the PISA results, this report calls attention to the need for improved student learning in Colombia and provides new analytical work on the factors associated with learning in Colombia and other participant countries. Based on an assessment of the current state of the Colombian education system (chapter first), a review of the relevant literature (chapter second), an analysis of PISA (chapter third), and the report concludes with a set of policy options that may inform a future agenda for system design and reform (chapter fourth).